Rapd-Pcr Based Genetic Relationship Of Muscid Flies (Diptera: Muscidae - MALVIYA S.; BAJPAI, N.; TEWARI, R.R. (International Journal of Pharma and Bio Sciences, 2012)
Random Amplified Polymorphic DNA-Polymerase Chain Reaction (RAPD-PCR) technique has been used in the present study to investigate genetic relationship between the two muscids viz., housefly Musca domestica Linnaeus and Lispe orientalis (Wiedemann). Tools for Population Genetic Analysis (TFPGA) software, was used to calculate genetic identity and distance, using data matrix prepared by the presence and absence of the bands generated by each primer. Average heterozygosity ranges from 0.156 to 0.301. The Nei’s genetic identity was 0.322, which revealed rather low genetic identity between the two species.